A composite matrix of mm-wave antenna arrays for 5G applications - Zakaria, Zahriladha; Ibrahim, Islam M.; Farah, Nada I.; Ahmed, Mohamed Ismail; AbdelKader, Hala M.; Al Gburi, Ahmed Jamal Abdullah; Elabd, Rania Hamdy; Elsherbini, Moataz M. (Wydawnictwo SIGMA-NOT, 2024)
This work designs, simulates, and fabricates a millimeter-wave antenna array for a 5G base station to support the significant improvements that come with the new 5G technology. The work starts with 1x8 arrays with sizes of 64.21.2 mm2 and 55x20.2 mm2 for 28 and 38 GHz, respectively. The elements are then increased to 8x8 arrays with dimensions of 64x169 mm2 for 28 GHz and 55x161.5 mm2 for 38 GHz. The proposed design is further promoted to a 16x8 array antenna with dimensions of 74x255x0.508 mm3. This antenna configuration initially consists of an 8x8 series-fed array operating at 28 GHz and another 8x8 operating at 38 GHz, all implemented on a Rogers/RT 5880 substrate with εr=2.2. At 28 GHz and 38 GHz, the radiation efficiency was measured to be 97.6% and 96.8%, respectively, and the greatest actual gain was 24.7 dBi. Additionally, the antenna array significantly boosts gain. The antenna's performance spans a dual-band millimeter-wave spectrum operating at 28–38 GHz. Specifically, at 28 GHz, 8x8 arrays have a realized gain of 20.33 dBi, and at 38 GHz, the gain is 22.23 dBi. Moreover, for the antenna range, the model displays a symmetrical radiation pattern, and the side lobe level is diminished to -10.2 dB. Two simulation programs, MWSCST2020, and ANSYS HFSS19, are used to simulate these array antennas. The simulation results closely match the actual model performance. Furthermore, the antenna is measured using an Agilent R&S Z67 VNA.